De um certo Poder… A Arquitectura e o Urbanismo como “Selos Monumentais” - Almeida, E. C. (Figuras & Negócios, 2023)
Abstract: Brief summary introduction: There is an unwritten rule that every administrative Power always likes to leave an urban or architectural mark for those it sees next and for its fellow citizens to “marvel at”. It is something that already comes from human ancestry. It's something irresistible! And this can be assessed in a simple and broad phrase for government power, by Brazilian architect Priscila Prestes «Architecture doesn’t just build things. It raises dreams and sustains memories»